Polycystic echinococcosis in Colombia: The larval cestodes in infected rodents - Morales, Gustavo A.; Guzmán, V.H.; Wells, Eric Arthur; Angel, D.I. (Wildlife Disease Association, 1979)
Described are the characteristics of the polycystic larval cestodes found in an endemic area of echinococcosis in the Easter Plains of Colombia and the tissue reaction evoked in infected rodents. Of 848 free-ranging animals examined, polycystic hydatids were found in 44/93 Cuniculus paca and 1/369 Proechimys sp. None of 20 Dasyprocta fuliginosa examined was infected, but hunters provided a heart with hydatid cysts and information about two additional animals with infected livers. Recognition of an endemic area of polycystic echinococcosis provides a means to investigate the life cycle of the parasites and to study the histogenesis of the larval cestodes in susceptible laboratory animals.